ANALYSIS OF THE POWER OF ONLINE TICKET LAWS IN PROVIDING CONVENIENCE FOR TRAFFIC OFFENDERS - Maulida Fitri; Muhamad Zainuri; RAHMAT HIDAYAT (Lembaga Penerbitan Jurnal Ilmiah Institut Agama Islam Bani Fattah Jombang, 2023)
One of the most frequent and easily identifiable legal violations is traffic violations. Traffic violations are a common phenomenon in large cities in developing countries like Indonesia. The problem addressed in this journal article is: what is the accountability of traffic violators? What is the legal power of the online ticketing system in facilitating traffic violators, and what are the efforts to combat traffic violations? The research is based on normative juridical methodology and empirical approaches, with data obtained from literature sources such as secondary and primary data through qualitative analysis to obtain accurate and objective research results. The research findings show that the accountability of traffic violators is adjusted according to the decision of the judge's council that the perpetrator has been proven legally and convincingly guilty of traffic violations, with a fine of IDR 49,000 (forty-nine thousand rupiahs), and the defendant must pay a case fee of IDR 1,000 (one thousand rupiahs). The legal power of online ticketing provides convenience for traffic violators who can pay fines through mobile or e-banking to BRI Bank accounts that have been appointed and serve as valid proof, which will later be transferred to the prosecutor's office without having to go directly to court or the prosecutor's office. Efforts to address traffic violations in the Tulang Bawang Police Resort area are taken through several steps, including pre-emptive measures such as socialization or counseling to the community about proper driving manners, preventive measures such as operations to identify drivers who do not have official documents, and repressive measures such as chasing and arresting perpetrators who flee after committing traffic violations, conducting investigations and prosecutions against perpetrators of traffic violations. The author suggests increasing public awareness and encouraging compliance with traffic laws through continued socialization of E-Ticketing by the Tulang Bawang Police Traffic Unit.